Steinbeck House, Salinas, California - Kjysten Drew:::Creator::::::::::::
Steinbeck House. 132 Central Avenue, Salinas, California. Built in 1897 in Queen Anne-style, purchased by the Steinbecks in 1900. John Steinbeck was born in the bedroom to the left of the entrance. Original is slide.